Financial dependence in early motherhood: experiences of young mothers in Lomahasha, Eswatini - Tsabedze, Busisiwe Prudence (My University, 2021)
Early motherhood is a major reason why most girls in Eswatini and some parts of the world do not finish school. The disruption in young mothers’ education significantly influences the cycle of poverty and financial dependence experienced by their families and communities. The aim of the study was to explore the experiences of young mothers regarding financial dependence, by using a qualitative approach and employing a narrative inquiry design. In exploring their experiences, the researcher wanted to gain a deeper understanding of the challenges and opportunities perceived by young mothers in achieving financial independence. The sample comprised 20 young mothers aged 20–24 years, who had their first child before the age of 20. Semi-structured interviews were used to collect data, which was transcribed and analysed using thematic analysis. The findings from this study demonstrate that the context in which motherhood occurs shapes young mothers’ experiences of motherhood. These mothers’ narratives reveal how contextual factors, including poverty, society, culture, and their partner’s reaction influenced their self-perception and their overall experience of motherhood. The findings highlighted the numerous challenges that financial dependence presented, its effect on their physical, psychological and emotional well-being, and its influence on their decision making. Despite the challenges of financial dependence in early motherhood, the young mothers’ narratives revealed a high regard for education and training and, generally, a high level of optimism about their future. As part of the recommendations, the prevention of unwanted pregnancy and breaking the cycle of poverty emerged as critical factors in dealing with this social issue. Further research is recommended to find solutions to alleviate the problem of teenage motherhood including its effect at individual, family and community level
A report on a research study presented to the Department of Social Work, School of Human and Community Development, Faculty of Humanities, University of the Witwatersrand in partial fulfilment of the requirements for the degree Master of Arts in Social Development, 2021